Social pensions and intimate partner violence against older women - Cristina Bellés-Obrero; Giulia La Mattina; Han Ye (Inter-American Development Bank (IDB), 2024)
The prevalence and determinants of intimate partner violence (IPV) among older women are severely understudied. This paper documents that the incidence of IPV remains high at old ages and provides the first evidence of the impact of access to income on IPV for older women. We leverage a Mexican reform that lowered the eligibility age for a non-contributory pension and a difference-in-differences approach. Women's eligibility for the pension increases their probability of being subjected to economic, psychological, and physical IPV. The estimated effects are found only among women in the short-term and are more pronounced for women who experienced family violence in childhood and those from poorer households. In contrast, we show that IPV does not increase when men become eligible for the non-contributory pension. Looking at potential mechanisms, we find suggestive evidence that men use violence as a tool to control women's resources. Additionally, women reduce paid employment after becoming eligible for the pension, which may result in more time spent at home and greater exposure to violent partners.
Keywords: I100; I120; I140; I31; 330; Non-contributory pension; Intimate partner violence; Retirement; Income